RANCANG BANGUN REPOSITORY PROGRAM STUDI TEKNIK INFORMATIKA BERBASIS WEB MENGGUNAKAN FRAMEWORK CODEIGNITER - Muhammad Widianto Oktori; Diki Gita Purnama (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2023)
This research was conducted to design and build a repository system for the informatics engineering study program at Paramadina University. Repository is a container for documenting and preserving digital information that is used through the internet network. The repository for collections in digital form produced by students and lecturers from the Informatics Engineering study program at Paramadina University is still ongoing along with other study programs. To search for scientific publication files the user must search for the name of the lecturer or student. Based on these problems, this prompted the author to develop a special repository application for the informatics engineering study program which was built using the waterfall method, in which the hope of forming this repository application can make it easier for lecturers and students to document and search for references to scientific publications or other documents.